The impact of mathematical competences and cognitive effort on the appearance of the framing effect - Kaczmarek, Aleksander; Przybyszewski, Krzysztof; Rutkowska, Dorota; Sosnowska, Honorata (Economics and Business Review, 2018)
The aim of this paper is to check whether mathematical competences influence some manifestations of bounded rationality. A special example of bounded rationality called “framing effect” is dealt with to analyze empirically the thesis that mathematical competences and cognitive effort may reduce the framing effect. Two kinds of cognitive effort: probabilistic and deductive are analysed. Experiments were conducted using samples of Polish students, both mathematically and business oriented. As an example of a framing situation an example called “Asian disease”, (the first analyzed and the most popular example of the framing effect), is considered. The thesis that a mathematical background may diminish the occurrence of the framing effect was partly confirmed.